Is the decolonization of the pedagogy possible? - Peñuela, Diana Milena (Universidad Pedagógica y Tecnológica de Colombia, 2010)
Which are the places for knowledge’s statement, production and legitimization from the pedagogy in Latin America? It is possible to change the knowledge`s ethics and policies that have been established in the colonialism and imperial post-colonialism’s logic following Mignolo? Which are the forms and the locus of knowledge and pedagogic thought’s production in Colombia and in Latin America? Which are the points of escape for the political statement from the pedagogy, from his historicity in Latin America? Is an effort to contribute with some elements of analysis to the functioning of the pedagogy inside the project modernity – post-modernity in Latin America from the de-colonial perspective’s studies. In addition, it tries to place the discussion in the historical frame of the pedagogic Latin-American thought, recapturing the contributions of Freire, Dussel and some authors of the critical pedagogy, in a bet for the recognition of those pedagogic critical speeches, that can be considered able to institute practices, projects and mobilizations of resistance within the Latin-American pedagogic and educational field, but that in turn, can be differentiated from the de-colonial and postcolonial studies.